2022
DOI: 10.55606/jrik.v2i3.753
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Partisipasi Pemanfaatan Waktu Luang Dengan Kualitas Hidup Lanjut Usia

Abstract: Populasi lansia meningkat secara signifikan hampir di semua negara. Akan tetapi peningkatan  prevalensi dan angka harapan hidup yang lebih panjang tidak selalu diikuti dengan kualitas hidup yang lebih baik. Pemanfaatan waktu luang telah digunakan dalam berbagai penelitian baik didalam dan diluar negeri serta telah terbukti bermanfaat untuk meningkatkan kualitas hidup lansia. Penelitian ini bertujuan mengetahui hubungan partisipasi pemanfaatan waktu luang dengan kualitas hidup lanjut usia. Teknik pengumpulan da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The results showed that spiritual levels were associated with better cognitive levels in the elderly (Fung & Lam, 2013 3 above, it can be seen that the highest number of respondents in the elderly who participated in the utilization of leisure time in the medium category amounted to 48 respondents (94.1%) and there were no respondents who were categorized as low in leisure participation (0%). Participating in the utilization of leisure time is a predictor of achieving the quality of life of the elderly (Lee et al, 2014;Nurhidayah, 2018). Looking at this research data, an empowerment effort is needed so that the elderly have a higher will, ability and opportunity to participate in the use of free time.…”
Section: Characteristics Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that spiritual levels were associated with better cognitive levels in the elderly (Fung & Lam, 2013 3 above, it can be seen that the highest number of respondents in the elderly who participated in the utilization of leisure time in the medium category amounted to 48 respondents (94.1%) and there were no respondents who were categorized as low in leisure participation (0%). Participating in the utilization of leisure time is a predictor of achieving the quality of life of the elderly (Lee et al, 2014;Nurhidayah, 2018). Looking at this research data, an empowerment effort is needed so that the elderly have a higher will, ability and opportunity to participate in the use of free time.…”
Section: Characteristics Ofmentioning
confidence: 99%
“…A significant increase in the elderly population occurred in almost all countries (Nurhidayah, 2018). Similarly, the number of elderly in Indonesia shows an increase from year to year.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations